(untitled) - Bruster, Douglas (New York, 2003)
This text presents a cultural analysis of Shakespeare's works and other early modern literature. Contending that recent "thick" historical criticism has gone too far in the direction of the local and peculiar, Bruster (U. of Texas) offers a "thin" description of culture that incorporates a broader range of contextual elements than New Historicism commonly employs. Early chapters are devoted to such topics as print culture in late- Elizabethan England and female-on-female eroticism in the theater, while the final three analyze how prominent critical schools shape our reading of literature
Keywords: Shakespeare, William, 1564-1616,English literature,Literature and history,Literature and history,Historicism in literature; Criticism and interpretation,History,Early modern, 1500-1700,History and criticism,Theory, etc.,History,16th century,History,17th century; England,England